ArrhythmoGenoPharmacoTherapy - Tosaki, Arpad (Frontiers in Pharmacology, 2020)
This review is focusing on the understanding of various factors and components governing and controlling the occurrence of ventricular arrhythmias including (i) the role of various ion channel-related changes in the action potential (AP), (ii) electrocardiograms (ECGs), (iii) some important arrhythmogenic mediators of reperfusion, and pharmacological approaches to their attenuation. The transmembrane potential in myocardial cells is depending on the cellular concentrations of several ions including sodium, calcium, and potassium on both sides of the cell membrane and active or inactive stages of ion channels. The movements of Na+, K+, and Ca2+ via cell membranes produce various currents that provoke AP, determining the cardiac cycle and heart function. A specific channel has its own type of gate, and it is opening and closing under specific transmembrane voltage, ionic, or metabolic conditions. APs of sinoatrial (SA) node, atrioventricular (AV) node, and Purkinje cells determine the pacemaker activity (depolarization phase 4) of the heart, leading to the surface manifestation, registration, and evaluation of ECG waves in both animal models and humans. AP and ECG changes are key factors in arrhythmogenesis, and the analysis of these changes serve for the clarification of the mechanisms of antiarrhythmic drugs. The classification of antiarrhythmic drugs may be based on their electrophysiological properties emphasizing the connection between basic electrophysiological activities and antiarrhythmic properties. The review also summarizes some important mechanisms of ventricular arrhythmias in the ischemic/reperfused myocardium and permits an assessment of antiarrhythmic potential of drugs used for pharmacotherapy under experimental and clinical conditions.